Optimalisasi Edukasi Sanitasi Lingkungan melalui Pemanfaatan Sampah Non-Organik untuk Mendukung Sustainable Development Goal #6 - Murniwati Murniwati; M Rahmatullah; Suhria Suhria; Jusran Jusran; Sitti Maifa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
−This program was conducted at SMP Negeri 3 Pulau Laut Tengah, Kotabaru Regency, South Kalimantan. The partner school faced challenges related to students’ limited awareness of environmental sanitation and waste management within the school environment. Preliminary observations indicated that various types of non-organic waste such as plastic, cardboard, straws, and food packaging were still found scattered in several areas of the school. This condition suggested that students’ understanding of environmental sanitation and waste management needed to be strengthened through participatory educational activities. The purpose of this community service program was to enhance students’ understanding of environmental sanitation and to provide direct learning experiences through creative recycling activities using non-organic waste materials. The activity employed an educational and participatory project-based approach involving 54 students from grades VII and VIII. The program was implemented through several stages, including the delivery of educational materials on environmental sanitation, interactive discussions, an evaluation quiz, and practical activities involving the reuse of non-organic waste to produce simple handicrafts. The results showed that most students were able to understand the material presented, as indicated by quiz results with correct response rates ranging from 74 percent to 100 percent. In addition, the recycling practice encouraged students to recognize that waste materials could be reused and transformed into useful products. The program not only improved students’ initial understanding of environmental sanitation but also provided valuable learning experiences for university students who served as facilitators in the activity. Overall, the program contributed to raising environmental awareness among students and supported the achievement of Sustainable Development Goals (SDGs), particularly Goal 6 on clean water and sanitation